Sociology of diagnosis - McGann, P. J.; Hutson, David J.; Rothman, Barbara Katz (Advances in medical sociology, 2011)
This is the only book to provide a comprehensive introduction to the sociology of diagnosis through original theoretical and empirical work by established and emerging scholars and, as such, it is poised to become a touchstone volume. Sixteen articles are presented across four sections. 'Power and the Politics of Diagnosis' explores diagnosis as a process of definition that includes: labeling dynamics between 'diagnoser' and diagnosed; boundary struggles between diverse constituents - both among medical practitioners and between medical authorities and others (such as lay persons, legal, religious, and/or governmental agents); and, the symbolic and material interests behind contested diagnoses. 'Identity, Experience, and Action' analyzes the impact of diagnosis on individual identity and illness experience, diagnosis as a basis for collective identity, and social action in relation to diagnoses. 'Diagnosis and Social Control' considers the role of diagnosis in norm enforcement and the production of moral boundaries and social standards, and diagnosis in relation to medicalization. 'Nosological Dynamics' explores diagnoses as socio-politico entities embedded in social relations.